Effect of In-Person and E-Training on Nurse Managers\' Perception of Patient Safety Culture in Hospitals of the Golestan Province, Iran - Gholamreza Mahmodi Shan; Zahra Royani; Farhad Kord; Sakine Beygom Kazemi; Samieh Ghana; Shima Rahimian; Soheyla Kalantary; Navisa Seyed Ghasemi (Journal of Clinical and Basic Research, 2019)
Background and objectives: Patient safety culture is one of the basic principles of health care. Nurses are the first to be involved in the implementation of this culture in clinical settings. The aim of this study was to determine effect of in-person and E-training on patient safety culture of nurse managers working in hospitals affiliated to the Golestan University of Medical Sciences, Golestan Province, Iran. Methods: This semi-experimental study was conducted on 60 nurse managers working in hospitals affiliated to the Golestan University of Medical Sciences in 2012. The subjects were randomly divided into an in-person training group and an E-training group. Data were collected using the patient safety culture questionnaire (originally designed by Liane Ginsburg). SPSS (version 16) was used for analysis of data using descriptive and inferential statistics. Results: After the training intervention, the patient safety culture improved significantly in both groups (P<0.001). However, the mean score of patient safety culture in the in-person training group was significantly higher than that in the E-training group (P<0.03). Conclusion:  The results of this study showed that both training programs are beneficial for promoting the patient safety culture in nurse managers. Since the support, commitment and understanding of hospital managers are crucial for creating a positive safety culture, managers can provide planned strategies for improving patient safety.